IMF Staff papers : Volume 43 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1996)
This paper reviews recent theoretical and empirical work on controls over International capital movements. Theoretical contributions reviewed focus on 'second-best ' arguments for capital market restrictions, as well as arguments based on multiple equilibria. The empirical literature suggests that controls have been 'effective ' in the narrow sense of influencing yield differentials. But there is little evidence that controls have helped governments meet policy objectives, with the exception of reducing the governments' debt-service costs, and no evidence that controls have enhanced economic welfare in a manner suggested by theory.